Unlocking Economic Growth in Dairi Regency through Tourism and Culture - Pinere , Rony; Simbolon, Romasinta; Monteiro, Juliana Maya (Insan Akademika Publications, 2022)
Dairi Regency, a region nestled in the natural splendor of North Sumatra, holds the promise of becoming an economic hub, fueled by the strategic development of tourism and culture. This research explores the multifaceted strategies necessary to enhance Original Regional Income by leveraging the wealth of cultural heritage and the allure of natural beauty. Cultural preservation and promotion emerge as key drivers of this transformation, recognizing the value of the unique Batak culture in attracting tourists seeking authentic experiences. Infrastructure development is an essential foundation, as improved connectivity and accommodations facilitate access to Dairi Regency's cultural and natural treasures, fostering tourism and economic growth. The path to a more inclusive and sustainable future is illuminated by community-based tourism (CBT). Engaging local communities in tourism activities and decision-making processes ensures equitable distribution of tourism benefits and enhances the region's authenticity. Diversification of tourism products broadens the audience, welcoming travelers with diverse preferences. The research outlines a structured planning approach, guided by SWOT analysis, enabling adaptive strategies that align with changing circumstances. Balanced spatial development, driven by GIS analysis insights, ensures economic prosperity is distributed evenly across the region. Sustainability and responsible tourism practices underline the importance of ethical and environmentally conscious tourism, contributing to long-term success. Collaboration between the community and government agencies strengthens the region's commitment to collective ownership of economic development. Transparent measurement of economic impact fosters trust and engagement. This research not only unveils the untapped potential of Dairi Regency but also presents a comprehensive roadmap for realizing this potential. It provides insights and strategies for the Tourism and Culture Department, local authorities, and stakeholders to shape a sustainable, inclusive, and culturally rich economic future for the region.